Evaluation of Olive and Palm Byproducts in Feeding Camels - Mahmoud, A.E.M.; El-Bana, H.M. (Pakistan Journal of Nutrition, 2013)
Metabolism trials were carried out using four mature males of Sudanese camels; Camelius dromedaries to evaluate the nutritive value of date stone (DS) and olive cake (OC), palm leaves (PL) and barley grains (BG) or their mixture. Results indicated that barley grains showed significantly (p